Common myths and misconceptions about breast cancer causation among Palestinian women: a national cross-sectional study - Mohamedraed Elshami; Islam Osama Ismail; Mohammed Alser; Ibrahim Al-Slaibi; Roba Jamal Ghithan; Faten Darwish Usrof; Malak Ayman Mousa Qawasmi; Heba Mahmoud Okshiya; Nouran Ramzi Shaban Shurrab; Ibtisam Ismail Mahfouz; Aseel AbdulQader Fannon; Mona Radi Mohammad Hawa; et al. (BMC Public Health, 2023)
Abstract Background The discussion about breast cancer (BC) causation continues to be surrounded by a number of myths and misbeliefs. If efforts are misdirected towards reducing risk from false mythical causes, individuals might be less likely to consider and adopt risk-reducing behaviors for evidence-based BC causes. This national study aimed to assess the awareness of BC causation myths and misbeliefs among Palestinian women, and examine the factors associated with having good awareness. Methods This national cross-sectional study recruited adult women from government hospitals, primary healthcare centers, and public spaces in 11 governorates in Palestine. A modified version of the Cancer Awareness Measure-Mythical Causes Scale was used to collect data. The level of awareness of BC causation myths was determined based on the number of myths recognized to be incorrect: poor (0–5), fair (6–10), or good (11–15). Results A total of 5,257 questionnaires were included. Only 269 participants (5.1%) demonstrated good awareness (i.e., recognizing more than 10 out of 15 BC mythical causes). There were no notable differences in displaying good awareness between the main areas of Palestine, the Gaza Strip and the West Bank and Jerusalem (5.1% vs. 5.1%). Having chronic disease as well as visiting hospitals and primary healthcare centers were associated with a decrease in the likelihood of displaying good awareness. Myths related to food were less frequently recognized as incorrect than food-unrelated myths. ‘Eating burnt food’ was the most recognized food-related myth (n = 1414, 26.9%), while ‘eating food containing additives’ was the least recognized (n = 599, 11.4%). ‘Having a physical trauma’ was the most recognized food-unrelated myth (n = 2795, 53.2%), whereas the least recognized was ‘wearing tight bra’ (n = 1018, 19.4%). Conclusions A very small proportion of Palestinian women could recognize 10 or more myths around BC causation. There is a substantial need to include clear information about BC causation in future educational interventions besides focusing on BC screening, signs and symptoms, and risk factors.